Analysis and treatment of the conflict between sustainable development and environmental protection based on the ecotourism concept - Tian, Jing; Li, Jing (Frontiers in Environmental Science, 2022)
With the rapid development of the global economy over the past few decades, tourism has greatly influenced economic internationalization and has become one of the top sectors. Meanwhile, during the development of tourism, serious environmental pollution and excessive energy resource consumption also occur, which is disadvantageous for the health of the global ecological environment as well as sustainable development. Against the background of increasing environmental pollution in the course of tourism development, some researchers began to introduce the ecosystem concept and emphasized the need for the construction of ecosystem models, especially those based on environmental protection, to satisfy the psychological needs of tourists and self-similarity and development of ecological institutions. However, many conflicts exist between sustainable ecosystem development and environmental protection. To realize a healthy and sustainable development of tourism and international ecological culture, this paper discusses the conflict between the concepts of ecosystem, sustainable development, and environmental protection, proposes some methods to improve the comprehensive benefits of ecotourism, and provides some suggestions for the development of ecotourism in China. This will help us achieve the sustainable use of resources and sustainable development of tourism.